Incident type 2 diabetes and hip fracture risk: a population-based matched cohort study. - Martinez-Laguna, D; Tebe, C; Javaid, M; Nogues, X; Arden, N; Cooper, C; Diez-Perez, A; Prieto-Alhambra, D (Springer London, 2015)
There is scarce data on the association between early stages of type 2 diabetes and fracture risk. We report a 20 % excess risk of hip fracture in the first years following disease onset compared to matched non-diabetic patients. INTRODUCTION: Type 2 diabetes mellitus (T2DM) is a chronic disease that affects several target organs. Data on the association between T2DM and osteoporotic fractures is controversial. We estimated risk of hip fracture in newly diagnosed T2DM patients, compared to matched non-diabetic peers. METHODS: We conducted a population-based parallel cohort study using data from the Sistema d'Informació per al Desenvolupament de la Investigació en Atenció Primària (SIDIAP) database. Participants were all newly diagnosed T2DM patients registered in SIDIAP in 2006-2011 (T2DM cohort). Up to two diabetes-free controls were matched to each T2DM participant on age, gender, and primary care practice. Main outcome was incident hip fracture in 2006-2011, ascertained using the tenth edition of the International Classification of Diseases (ICD-10) codes. We used Fine and Gray survival modelling to estimate risk of hip fracture according to T2DM status, accounting for competing risk of death. Multivariate models were adjusted for body mass index, previous fracture, and use of oral corticosteroids. RESULTS: During the study period (median follow-up 2.63 years), 444/58,483 diabetic patients sustained a hip fracture (incidence rate 2.7/1,000 person-years) compared to 776/113,448 matched controls (2.4/1,000). This is equivalent to an unadjusted (age- and gender-matched) subhazard ratio (SHR) 1.11 [0.99-1.24], and adjusted SHR 1.20 [1.06-1.35]. The adjusted SHR for major osteoporotic and any osteoporotic fractures were 0.95 [0.89-1.01] and 0.97 [0.92-1.02]. CONCLUSIONS: Newly diagnosed T2DM patients are at a 20 % increased risk of hip fracture even in early stages of disease, but no for all fractures. More data is needed on the causes for an increased fracture risk in T2DM patients as well as on the predictors of osteoporotic fractures among these patients.